Digitalization of Marketing in Amadanom Dampit Coffee SMEs - Rezhania Jelly Kriteria (Green Publisher Indonesia, 2021)
This study aims to determine and analyze how the application of digitalization of marketing in Small and Medium Enterprises Coffee Amadanom in Dampit District, Malang Regency. This research is a research with a qualitative descriptive approach. Researchers want to do research with a natural background or according to the existing context. The researcher wants to reveal the facts related to marketing management in an effort to digitize marketing in the Amadanom Coffee Small and Medium Enterprises, Dampit District. Sources of research data obtained through interviews and observations on six specified informants. The results showed that online marketing activities were carried out very well in UKM Tani Harapan. Offline and online marketing play a role in supporting business marketing. The application of online marketing has a significant impact on increasing income every year. With the implementation of digital marketing, the company's goals are easier to achieve and facilitate integration with other companies. It can be concluded that the application of digital marketing not only facilitates marketing activities carried out by business units but also improves the cooperative relationship between these business units and other business actors.